JEJAK KOLONIALISME DALAM PENDIDIKAN ISLAM DI INDONESIA: DARI TANTANGAN HINGGA TRANSISI - Ratna Kasni Yuniendel (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Islamic education in Indonesia has experienced a dynamic development since the pre-colonial period through traditional institutions such as pesantren, surau, and madrasah that functioned as centers of religious and moral education. The arrival of Dutch colonialism changed the course of Islamic education through discriminatory policies aimed at reducing its influence in indigenous society. Colonialism introduced a more controlled Western education system and sidelined Islamic education, which had to adapt amidst the pressure. Despite facing many obstacles, Islamic education played a significant role in awakening the spirit of nationalism and became a means of resistance against colonialism. After independence, Islamic education transitioned into a more inclusive national system, although it still faces the challenge of maintaining Islamic values amid globalization. This research focuses on the traces of colonialism in Islamic education in Indonesia, examining its impact on the structure of education as well as the adaptation process that continues to this day. Through this historical analysis, it is hoped that a deeper understanding of the role of Islamic education in building national identity and the development of relevant educational policies will emerge.